The Influence of Dosing Modes of Coagulate on Arsenic Removal - Zhibin Zhang; Jinxiang Li; Cuizhen Sun; Yanhao Zhang; Lilong Huang; Meng Wang (Journal of Chemistry)
Three different dosing modes, including one single dosing mode and two sequential dosing modes, were applied in high-arsenic contaminated water treatment. The results illustrated that the As (V) soluble and the As (V) nonspecifically sorbed were the insignificant species from Fe-As (V) samples in the sequential dosing mode, while they were higher in the single dosing mode. However, it could be further concluded that the mobility of the Fe-As (V) in sequential dosing mode was greater than that in single dosing mode. Besides, the main arsenic speciation governing the arsenic-borne coagulates was the As (V) associated with poorly crystalline hydrous oxides of Fe in sequential or single dosing mode. Moreover, the particle size distribution analysis indicated that the sequential dosing mode was more prevalent in neutralizing and adsorbing the As (V) compared with the single dosing mode. In the FT-IR spectra, the presence of arsenic was highlighted by a well resolved band at 825–829 cm−1. The positions of the As–O stretching vibration bands were shifted gradually as the dosing mode changed from the single to the sequential. This result could be related to the distribution of arsenic speciation in different dosing modes.